Entrepreneurship in the digital era - Achmad, Nur; Saputro, Edy Purwo; Handayani, Sih (Dinamika Pendidikan, 2016)
Entrepreneurship was one of the key issues related to many aspects, including its relevance to the economic, business and employment. The researches on entrepreneurship were the references to identify the success factors which supported the entrepreneurial success. The internet development in the digital age indirectly influenced the entrepreneurial ethos. It was not only influenced by the market potential and product innovation, but also by the commitments to entrepreneurship education and training model. Therefore, the studies on entrepreneurship in the industrial and developing countries were attractive. It was relevant to the internet era which provided opportunities for the development of entrepreneurial ethos, especially for the younger generation.